2013
DOI: 10.4149/bll_2013_088
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of coronary vessel involvement on the basis of atherosclerosis risk factor analysis

Abstract: The prediction of coronary vessel involvement by means of noninvasive tests is one of the fundamental objectives of preventive cardiology. This review describes the current possibilities of coronary vessel involvement prediction by means of ultrasonographic examination of carotid arteries, analysis of polymorphisms in the genes encoding enzymes responsible for production of nitric oxide and carbon monoxide and assessment of levels of certain proinfl ammatory cytokines. In the presented work these noninvasive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Full articles were obtained for the remaining 20 publications. According to the inclusion criteria, nine articles were excluded, with five articles excluded for conducting subgroup or post hoc analysis of included studies (Tsujita et al, 2016a;Tsujita et al, 2016b;Kovarnik et al, 2017;Fujisue et al, 2018;Fujisue et al, 2021), and four excluded for comparing the impact of ezetimibe-statin combination treatment versus statin monotherapy through IVUS examination without reporting data on TAV or LV (Wang et al, 2016;Ueda et al, 2017;Zhao et al, 2021;Nakano et al, 2023). No further eligible papers were obtained from the bibliographies of the included studies.…”
Section: Trial Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Full articles were obtained for the remaining 20 publications. According to the inclusion criteria, nine articles were excluded, with five articles excluded for conducting subgroup or post hoc analysis of included studies (Tsujita et al, 2016a;Tsujita et al, 2016b;Kovarnik et al, 2017;Fujisue et al, 2018;Fujisue et al, 2021), and four excluded for comparing the impact of ezetimibe-statin combination treatment versus statin monotherapy through IVUS examination without reporting data on TAV or LV (Wang et al, 2016;Ueda et al, 2017;Zhao et al, 2021;Nakano et al, 2023). No further eligible papers were obtained from the bibliographies of the included studies.…”
Section: Trial Flowmentioning
confidence: 99%
“…Lumen stenosis of the target coronary artery plaque lesion was further evaluated by LV through examination with IVUS. Eight studies with 724 individuals (358 in the lipid-lowering therapy group and 365 in the statin monotherapy group) were available at the last follow-up, which included the change from baseline in LV as an outcome (Nakajima et al, 2014;Masuda et al, 2015;Tsujita et al, 2015;Lee et al, 2016;Hougaard et al, 2017;Kovarnik et al, 2017;Hibi et al, 2018;Oh et al, 2021). With the pooled WMD of −0.52 (95%CI: 2.24 to 1.21), it was indicated that ezetimibe-statin combination therapy and statin monotherapy had a similar effect on lumenal stenosis of coronary artery (p = 0.56), and the outcome is summarized in Figure 3B.…”
Section: Intravascular Ultrasound (Ivus) Findingsmentioning
confidence: 99%